The Application of AIR Learning Model to Increase Junior High School Students Mathematical Communication Ability - Sri Rohayati (Universitas Jambi, 2018)
Abstrak Kemampuan komunikasi matematika siswa di SMP 1 Cilaku masiih rendah karena terbatasnya model pembelajaran yang digunakan dalam proses pembelajaran matematika. Proses pembelajaran biasa didominasi oleh guru sehingga membuat siswa merasa jenuh, bosan, dan pembelajaran jadi terasa tidak menyenangkan. Tujuan penelitian ini adalah untuk meningkatkan kemampuan komunikasi siswa kelas Vii SMP 1 Cilaku di Cianjur menggunakan model AIR dan dapat meningkatkan aktivitas belajar siswa, menyampaikan pendapat dalam proses menyelesaikan masalah, keterampilan bertanya dan pengetahuan. Penelitian ini merupakan penelitian tindakan kelas dengan dua siklus pada siswa kelas VII D di SMP 1 Cilaku tahun ajatan 2016-2017 sebagai objek penelitian. Terdapat pengaruh penerapan model pembelajaran AIR. Pembelajaran berjalan dengan kondusif sehingga siswa memberikan respon yang positif dan menunjukkan peningkatan pada setiap siklus. Kata Kunci: model Pembelajaran AIR, komunikasi matematika   The Application of AIR Learning Model to Increase Junior High School Students Mathematical Communication Ability   Abstract Mathematical communication ability among students in Cilaku 1 junior high school still low because of the lack of the learning models in mathematics lesson. The ordinary learning mostly dominated by the teacher that makes the students feel saturated, bored, and makes the lesson considered not fun. The aims of this research are to increase the students's mathematical communication ability grade VII in Cilaku 1 junior high school in Cianjur by using the AIR model and can increase the students's learning activity, the clear arguments in completion problem proccess, asking and knowledge skills. This research is action class research trough two cycles with students in D class grad VII in Cilaku 1 junior high school year 2016-2017 as the objects of the research. Significantly had done the lesson using AIR model. The lesson is condusive so that the students give positive response and shows increase in every cycles. Keywords : AIR learning model, mathematics communication